The Role of Primary Care in the Initiation of Opioid Use Disorder Treatment in Statewide Public and Private Insurance. Issue 2 (10th March 2022) - Gertner, Alex K.; Rotter, Jason S.; Holly, Margaret E.; Shea, Christopher M.; Green, Sherri L.; Domino, Marisa Elena
Abstract : Objective: To determine if individuals newly diagnosed with opioid use disorder (OUD) who saw a primary care provider (PCP) before or on the date of diagnosis had higher rates of medication treatment for OUD (MOUD). Methods: Observational study using logistic regression with claims data from Medicaid and a large private insurer in North Carolina from January 2014 to July 2017. Key Results: Between 2014 and 2017, the prevalence of diagnosed OUD increased by 47% among Medicaid enrollees and by 76% among the privately insured. Over the same time period, the percent of people with an OUD who received MOUD fell among both groups, while PCP involvement in treatment increased. Of Medicaid enrollees receiving buprenorphine, the percent receiving buprenorphine from a PCP increased from 32% in 2014 to 39% in 2017. Approximately 82% of people newly diagnosed with OUD had a PCP visit in the 12 months before diagnosis in Medicaid and private insurance. Those with a prior PCP visit were not more likely to receive MOUD. Seeing a PCP at diagnosis was associated with a higher probability of receiving MOUD than seeing an emergency provider but a lower probability than seeing a behavioral health specialist or other provider type. Conclusions: People newly diagnosed with OUD had high rates of contact with PCPs before diagnosis, supporting the importance of PCPs in diagnosing OUD and connecting people to MOUD. Policies and programs to increase access to MOUD and improve PCPs' ability to connect people to evidence-based treatment are needed.